Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
First simplify the expression into polynomial form,
[tex](x-1)(x-3)(x+5)(x+7)=297[/tex]
[tex]x^4+8x^3-10x^2-104x+105=297[/tex]
[tex]x^4+8x^3-10x^2-104x-192=0[/tex]
Now factor into,
[tex](x-4)(x+8)(x^2+4x+6)=0[/tex]
Which means the solutions are,
[tex]x-4=0\implies\boxed{x_1=4}[/tex]
[tex]x+8=0\implies\boxed{x_2=-8}[/tex]
and then two complex solutions because determinant of the third factor [tex]D\lt0[/tex],
[tex]x^2+4x+6=0[/tex]
[tex]x^2+4x+4=-2[/tex]
[tex](x+2)^2=-2\implies\boxed{x_3=i\sqrt{2}-2},\boxed{x_4=-i\sqrt{2}-2}[/tex]
Hope this helps :)
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.